Smith-Purcell radiation from a cylindrical grating; Charged and Neutral Particles Channeling Phenomena - Saharian A. A.; Mkrtchan (Mkrtchyan) A. R. Alpik Rafaelovich; Kotanjyan A. S.; Kachatryan B. V. (2016, 2016)
Title screen